Two new species of the genus Rhicnogryllus Chopard, 1925 from Hainan, China (Orthoptera: Trigonidiidae: Trigonidiinae) - Liu, Yi-Jiao; He, Zhu-Qing (Zootaxa, 2021)
Rhicnogryllus Chopard, 1925 currently comprises 13 extant species from Asia, Africa, South America and the Pacific. We describe two new species, R. xuandan He sp. nov. and R. fallax He sp. nov., from Hainan Island, China. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).